2017
DOI: 10.1016/j.medengphy.2017.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Total ankle replacement design and positioning affect implant-bone micromotion and bone strains

Abstract: HighlightsA finite element model was developed to calculate micromotion of ankle implants.Both optimally-positioned and malpositioned cases were considered.Fixation nearer to the joint line relying on plural pegs improved implant stability.Gaps between the implant and bone greatly increased micromotion and bone strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 49 publications
5
71
0
Order By: Relevance
“…The FE predicted bone strain and bone‐prosthesis interface micromotion results have shown a good correlation with the strain and interface micromotion values measured by in vitro cadaveric study, indicating the validity of the FE models generated and can be used for reliable TAR biomechanical study. The overall principal strains obtained in this study were well below the bone yield strains of 0.73% (−7300 με) (minimum principal strain) and 0.65% (6500 με) (maximum principal strain) . Potentially, the new PD Design (contralateral talus bone left) induced experimental and predicted principal strains that were essentially lower than the STAR Ankle talar component.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The FE predicted bone strain and bone‐prosthesis interface micromotion results have shown a good correlation with the strain and interface micromotion values measured by in vitro cadaveric study, indicating the validity of the FE models generated and can be used for reliable TAR biomechanical study. The overall principal strains obtained in this study were well below the bone yield strains of 0.73% (−7300 με) (minimum principal strain) and 0.65% (6500 με) (maximum principal strain) . Potentially, the new PD Design (contralateral talus bone left) induced experimental and predicted principal strains that were essentially lower than the STAR Ankle talar component.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, this study is important to understand the relative micromotion and minimum principal stress issues of the TAR with the scope of reducing the aseptic loosening risk. Results from this study have shown that the relative micromotion and minimum principal stress were greatly influenced by the complexity of the talar component design, loading conditions, and the gait cycles due to the meniscal bearing displacements compressing both the talar component and talus bone. This can be clearly seen from the contour plot results as shown in the Figure (BPIRM) and Figure (minimum principal stress).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Proper implant positioning is mandatory for achieving good clinical results in TAA [8,21,22]. Compared with total hip and knee, the ankle joint presents a smaller surface area for load transmission and may withstand up to 500% of body weight during level walking [23].…”
Section: Discussionmentioning
confidence: 99%